The prosody of interrogatives at transition-relevance places in Mandarin Chinese conversation - Xu, Jun (2008)
This study aims to address the issue of the extent to which prosody contributes to projecting possible turn endings in Mandarin Chinese conversation. The research specifically focuses on the realization of the pitch contour of the final syllable in yes/no questions, based on a small scale of study of eight map-task-type conversations. The examination of 62 ma-particle yes/no questions and 75 yes/no questions with the construction of ‘A-not-A’ or ‘Copula-NEG’ suggests falling intonation is the most prominent pitch contour in yes/no questions at ends of turns in map-task-type conversations in Mandarin Chinese. The analysis of my data has also shown that the yes/no interrogative might have a terminal level, and they may end in rising and falling. Another finding is that the underlying tone of the last toned syllable plays a crucial role on the surface of the final pitch movement of yes/no interrogatives ending with toned syllables. On the basis of this finding, inspection of the turn-final declarative demonstrates that the same final pitch patterns displayed in the ‘A-not-A’ interrogatives ending with toned syllables exist in the turn-final declaratives in my data.